2007
DOI: 10.1108/14636646200700024
|View full text |Cite
|
Sign up to set email alerts
|

Audit of the NICE Guidelines for Schizophrenia in an NHS forensic psychiatric service

Abstract: The NICE Guidelines for Schizophrenia are designed to give guidance on the best practice in treatment and management of schizophrenia. These guidelines have 13 standards which services can use for the purpose of audit. As schizophrenia is our service's most common diagnosis, an audit against the guidelines was undertaken. The results indicated that we met three of the standards. Recommendations have been implemented to improve practice on standards that were not met, and this has led to some creative practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The NICE glossary of study designs (National Institute for Health and Clinical Excellence, 2012) was used to classify identified papers into their different methodologies. Twelve were quantitative observational cross-section studies, five national audits (Healthcare Commission, 2007Rethink, 2008; The All Parliamentary Group on Mental Health, 2010; The Schizophrenia Commission, 2012) and seven local service audits (Gough et al, 2007;Haddock et al, 2014;Jolley et al, 2015;Kuipers, 2011;Lewis, , & Evenson, 2012;Macpherson, Hovey, Ranganath, Uppal, & Thompson, 2007;Pawel, Mankiewicz, & Turner, 2012), four were qualitative studies using a mixture of methods (Braehler & Harper, 2008;Fadden & Heelis, 2011;Michie et al, 2007;Williams, 2008), seven were a mixture of qualitative and quantitative cross-section studies (Bailey, Burbach, & Lea, 2003;Jolley et al, 2012;McCann & Bowers, 2005;Onwumere, Chung, Boddington, Little, & Kuipers, 2014;Prytys, Garety, Jolley, Onwumere, & Craig, 2011;Sin, Livingstone, Griffiths, & Gamble, 2014;Sin & Scully, 2008), two were randomized control trials (Ince, Tai, & Haddock, 2015;Michie & Lester, 2005), and one was a non-experimental cases study (Smith & Velleman, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NICE glossary of study designs (National Institute for Health and Clinical Excellence, 2012) was used to classify identified papers into their different methodologies. Twelve were quantitative observational cross-section studies, five national audits (Healthcare Commission, 2007Rethink, 2008; The All Parliamentary Group on Mental Health, 2010; The Schizophrenia Commission, 2012) and seven local service audits (Gough et al, 2007;Haddock et al, 2014;Jolley et al, 2015;Kuipers, 2011;Lewis, , & Evenson, 2012;Macpherson, Hovey, Ranganath, Uppal, & Thompson, 2007;Pawel, Mankiewicz, & Turner, 2012), four were qualitative studies using a mixture of methods (Braehler & Harper, 2008;Fadden & Heelis, 2011;Michie et al, 2007;Williams, 2008), seven were a mixture of qualitative and quantitative cross-section studies (Bailey, Burbach, & Lea, 2003;Jolley et al, 2012;McCann & Bowers, 2005;Onwumere, Chung, Boddington, Little, & Kuipers, 2014;Prytys, Garety, Jolley, Onwumere, & Craig, 2011;Sin, Livingstone, Griffiths, & Gamble, 2014;Sin & Scully, 2008), two were randomized control trials (Ince, Tai, & Haddock, 2015;Michie & Lester, 2005), and one was a non-experimental cases study (Smith & Velleman, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Ten articles provided information on the rates of implementation for CBT, estimates ranged from 4% to 100%; eight reported rates for FI, estimates ranged from 0% to 53% (Table 1). These included three national audits and surveys (Healthcare Commission, 2007Rethink, 2008) and seven local audits of services from various settings (Gough et al, 2007;Haddock et al, 2014;Kuipers, 2011;Lewis et al, 2012;Macpherson et al, 2007;Onwumere et al, 2014;Pawel et al, 2012;Prytys et al, 2011). Quality assessment revealed that only one study (Haddock et al, 2014) had a design that minimized the risk of bias to both internal and external validity.…”
Section: Buffhammentioning
confidence: 99%
See 1 more Smart Citation
“…One of the factors that may contribute to the variation in reported estimates is the criteria researchers use to decide whether a service user has been "offered" an intervention or not. Other possible reasons for varied reported implementation rates may include differences in the way data are collected, with some studies using objective measures (Haddock et al, 2014;Lewis, Buffham, & Evenson, 2012;Pawel et al, 2012) and others using subjective measures (Gough et al, 2007;Macpherson, Hovey, Ranganath, Uppal, & Thompson, 2008), studies not providing information regarding the data collection process (H. Commission, 2007;Kuipers, 2011;Prytys, Garety, Jolley, Onwumere, & Craig, 2011), and uncertainty regarding the criteria used to ascertain diagnosis. This highlights a common problem in many of the published papers reporting implementation figures: There is a lack of distinction between reports of services having been "offered," "delivered," or "received."…”
Section: Rates Of Implementation Of Fis For Schizophreniamentioning
confidence: 99%